Syndication of VCPE Investments: Evidence from the Indian Infrastructure Sector - Tripathi, Smita (Indian Journal of Finance, 2015)
In this paper, I examined the syndication of VCPE investments in the Indian infrastructure sector. Using a sample of 501 deals from 160 VCPE funds that happened during 2004 to 2013, the findings indicated that syndication was more pronounced when VCPE funds faced higher risk, and requirement of financial and human capital was larger. This study strongly supported the capital motive of syndication because the total size of investment was significantly higher in syndicated investments than in stand-alone investments. Moreover, I found that higher experienced VCPE funds were more open to syndication. Regression analysis of VCPE syndication indicated that due to less acquaintance with the Indian infrastructure sector and business environment, foreign VCPE investors faced higher risks and ,therefore, were more inclined to involve other VCPE funds to share knowledge base resources.